2015
DOI: 10.1016/j.devcel.2015.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Par-Polarized Cortical Domains via Phosphoregulated Membrane Motifs

Abstract: The Par polarity complex creates mutually exclusive cortical domains in diverse animal cells. Activity of the atypical protein kinase C (aPKC) is a key output of the Par complex as phosphorylation removes substrates from the Par domain. Here we investigate how diverse, apparently unrelated Par substrates, couple phosphorylation to cortical displacement. Each protein contains a basic and hydrophobic (BH) motif that interacts directly with phospholipids and also overlaps with aPKC phosphorylation sites. Phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(136 citation statements)
references
References 77 publications
6
130
0
Order By: Relevance
“…Consistently, a previous study demonstrated that the electrostatic-based interaction of N-WASP with PI(4,5)P2 is multivalent, and that this contributes both to the cooperativity of this protein-lipid interaction and to the ultrasensitive, switch-like kinetics of actin polymerization (Papayannopoulos et al, 2005). Multivalent protein-lipid interactions also underlie Par polarity complex localization to anionic lipids at the cortex, where basic-hydrophobic domains resemble the BC motifs that we identify in Bem1 (Bailey & Prehoda, 2015). Multivalent protein-lipid interactions also underlie Par polarity complex localization to anionic lipids at the cortex, where basic-hydrophobic domains resemble the BC motifs that we identify in Bem1 (Bailey & Prehoda, 2015).…”
Section: Of 19supporting
confidence: 90%
See 1 more Smart Citation
“…Consistently, a previous study demonstrated that the electrostatic-based interaction of N-WASP with PI(4,5)P2 is multivalent, and that this contributes both to the cooperativity of this protein-lipid interaction and to the ultrasensitive, switch-like kinetics of actin polymerization (Papayannopoulos et al, 2005). Multivalent protein-lipid interactions also underlie Par polarity complex localization to anionic lipids at the cortex, where basic-hydrophobic domains resemble the BC motifs that we identify in Bem1 (Bailey & Prehoda, 2015). Multivalent protein-lipid interactions also underlie Par polarity complex localization to anionic lipids at the cortex, where basic-hydrophobic domains resemble the BC motifs that we identify in Bem1 (Bailey & Prehoda, 2015).…”
Section: Of 19supporting
confidence: 90%
“…Since polarity establishment is also a switch-like process, it is conceivable that cooperativity in the Bem1-lipid interaction may contribute to these properties. Multivalent protein-lipid interactions also underlie Par polarity complex localization to anionic lipids at the cortex, where basic-hydrophobic domains resemble the BC motifs that we identify in Bem1 (Bailey & Prehoda, 2015). Similarly, multivalent protein-lipid interactions play a role in the recruitment of dynamin, EEA1, retromer, and ESCRT-III complexes to membranes (Lemmon & Ferguson, 2000;Seaman & Williams, 2002;Hayakawa et al, 2004;Buchkovich et al, 2013).…”
Section: Discussionsupporting
confidence: 55%
“…One breakthrough in recent studies is the identification of so-called polybasic (i.e. basichydrophobic) domains in several polarity proteins such as Lgl, Numb and Miranda (Bailey and Prehoda, 2015;Dong et al, 2015). Polybasic domains are short but highly positively charged due to the enrichment of basic Arg/Lys residues.…”
Section: Introductionmentioning
confidence: 99%
“…7A). Recently, studies on a biochemically diverse group of proteins from different organisms demonstrated that protein domains required for membrane association could be reliably predicted based on their basic and hydrophobic score (BH score) above a critical threshold value of 0.6 (Bailey and Prehoda, 2015;Brzeska et al, 2010). Accordingly, the biophysical properties, determined by, for example, the BH score rather than amino acid conservation, could control protein-membrane associations.…”
Section: D6pk Plasma Membrane Association Is Phospholipid Dependentmentioning
confidence: 99%